Application of plant extended phenotypes to manage the agricultural microbiome belowground - Favela, Alonso; Bohn, Martin O.; Kent, Angela D. (Frontiers in Microbiomes, 2023)
Plants have a surprising capacity to alter their environmental conditions to create adequate niches for survival and stress tolerance. This process of environmental transformation, commonly referred to as “extended phenotypes” or “niche construction”, has historically been studied in the domain of ecology, but this is a process that is pervasive across the plant kingdom. Furthermore, research is beginning to show that plants’ extended phenotypes shape the assembly and function of closely associated microbial communities. Incorporation and understanding the role that plant-extended phenotypes play in agriculture may offer novel, bioinspired methods to manage our arable soil microbiomes. Here, we review the challenges agriculture faces, the plant-extended phenotypes we know to shape the microbiome, and the potential utilization of this knowledge to improve the environmental impact of agriculture. Understanding how plant-extended phenotypes shape microbial communities could be a key to creating a sustainable future with both plants and microbiomes in consideration.